An ERP investigation of orthographic precision in deaf and hearing readers. (September 2020) - Meade, Gabriela; Grainger, Jonathan; Midgley, Katherine J.; Holcomb, Phillip J.; Emmorey, Karen
Abstract: Phonology is often assumed to play a role in the tuning of orthographic representations, but it is unknown whether deaf readers' reduced access to spoken phonology reduces orthographic precision. To index how precisely deaf and hearing readers encode orthographic information, we used a masked transposed-letter (TL) priming paradigm. Word targets were preceded by TL primes formed by reversing two letters in the word and substitution primes in which the same two letters were replaced. The two letters that were manipulated were either in adjacent or non-adjacent positions, yielding four prime conditions: adjacent TL (e.g., chikcen-CHICKEN ), adjacent substitution (e.g., chidven - CHICKEN ), non-adjacent TL (e.g., ckichen-CHICKEN ), and non-adjacent substitution (e.g., cticfen-CHICKEN ). Replicating the standard TL priming effects, targets preceded by TL primes elicited smaller amplitude negativities and faster responses than those preceded by substitution primes overall. This indicates some degree of flexibility in the associations between letters and their positions within words. More flexible (i.e., less precise) representations are thought to be more susceptible to activation by TL primes, resulting in larger TL priming effects. However, the size of the TL priming effects was virtually identical between groups. Moreover, the ERP effects were shifted in time such that the adjacent TL priming effect arose earlier than the non-adjacent TL priming effect in both groups. These results suggest that phonological tuning is not required to represent orthographic information in a precise manner. Highlights: Adjacent and non-adjacent transposed-letter priming assessed orthographic precision. Deaf and hearing participants were matched for age and spelling ability. No significant differences between groups in behavioral, N250, or N400 priming. Adjacent priming occurred earlier than non-adjacent priming in both groups. Spoken phonology is not a requirement for orthographic tuning.